2022
DOI: 10.1101/2022.10.31.514585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel anti-cancer therapy with nuclear export inhibitor Selinexor in combination with oncolytic myxoma virus

Abstract: Oncolytic viruses exploited for cancer therapy are developed to selectively infect, replicate, and kill cancer cells to stop tumor growth. However, in some cancer cells, oncolytic viruses are often limited in completing their full replication cycle, making progeny virions, and/or spread in the tumor bed due to the heterogeneous cell types within the tumor bed. Here we report that nuclear export pathway regulates oncolytic myxoma virus (MYXV) infection and cytoplasmic viral replication in a subclass of human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition, Selinexor treatment reduced the formation of cytoplasmic DHX9 antiviral granules, which are involved in lowering MYXV late protein synthesis and replication. Selinexor also enhanced the nuclear localization of DHX9 and, as predicted, blocked the XPO1-mediated export of DHX9 nuclear transport (26). These findings led us to investigate further the role of Selinexor-mediated inhibition of XPO1 nuclear export pathway on other viruses.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…In addition, Selinexor treatment reduced the formation of cytoplasmic DHX9 antiviral granules, which are involved in lowering MYXV late protein synthesis and replication. Selinexor also enhanced the nuclear localization of DHX9 and, as predicted, blocked the XPO1-mediated export of DHX9 nuclear transport (26). These findings led us to investigate further the role of Selinexor-mediated inhibition of XPO1 nuclear export pathway on other viruses.…”
Section: Introductionsupporting
confidence: 72%
“…We recently reported that, unlike RNA viruses, LMB or Selinexor enhances the replication of oncolytic MYXV, a leporipoxvirus developed for cancer treatment (26). In human cancer cells, Selinexor enhanced MYXV replication only at a low concentration that had minimal or no toxicity to the cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations